Pelatihan Pembuatan Water Kefir sebagai Minuman Probiotik - Caroline, Caroline; Ervina, Martha; Hadinugroho, Wuryanto; Esar, Senny Yesery; Wijaya, Hendy; Tjahjono, Yudi; Handayani, Yuliastuti Ika; Sutedja, Anita Maya (Universitas Baiturrahim, 2024)
Christ the King of Surabaya Parish through the Socio-Economic Development Section (PSE) in collaboration with Widya Mandala Catholic University Surabaya, was committed to assisting the Indonesian government's program in terms of improving the post-pandemic family economy through training in making health drinks from herbal ingredients, namely water kefir, which has been used as a probiotic drink. The training participants were underprivileged families in the Parish of Christ the King Surabaya. The training was carried out for 1 day with presentation of material by the team, training implementation and training evaluation by filling out pre-tests, post-tests and questionnaires as well as 30 days of assistance for participants who were interested in developing products to improve their economy. The results of the training show high enthusiasm from the participants, an increase in the knowledge of the participants which was marked by an increase in the value of the posttest compared to the pretest and the desire of the participants to produce and market products to improve the family economy